Transporters in plant sulfur metabolism - Gigolashvili, Tamara; Kopriva, Stanislav (Frontiers in Plant Science, 2014)
Sulfur is an essential nutrient, necessary for synthesis of many metabolites. The uptake of sulfate, primary and secondary assimilation, the biosynthesis, storage and final utilisation of sulfur (S) containing compounds requires a lot of movement between organs, cells, and organelles. Efficient transport systems of S-containing compounds across the internal barriers or the plasma membrane and organellar membranes are therefore required. Here, we review a current state of knowledge of the transport of a range of S-containing metabolites within and between the cells as well as of their long distance transport. An improved understanding of mechanisms and regulation of transport will facilitate successful engineering of the respective pathways, to improve the plant yield, biotic interaction and nutritional properties of crops.